PENGEMBANGAN LEMBAR KERJA SISWA MATERI PERKALIAN MATRIKS BERCIRIKAN PENEMUAN TERBIMBING UNTUK SISWA SMK KELAS X - Kiki Fauziah; I Nengah Parta; Swasono Rahardjo (Graduate School of Universitas Negeri Malang, 2016)
This development research aims to develop student's worksheet matrix multiplication-based guided discovery in class X SMK valid, practical, and effective. The development of this student worksheets using the 4-D model of development that consists of four stages, but in the development of the student worksheet is only going to be done until the third stage only. The subject of trials on the research development of this student worksheets are grade X SMK Putra Indonesia Malang. Based on the results of the validation of worksheets students validated by the three validator experts and practitioners, the student worksheet developed meet the category is valid. Based on the results of observation of its student worksheet demonstrates that levels of student worksheet demonstrates reach the high category, so the student worksheet developed meet the practical category. Average rating based on mastery of the whole class learning materials namely 76, guided discovery that include categories and student response against the student worksheet include positive categories, so the student worksheet developed meet the category effectively. Thus the student worksheets multiplication matrix-based discovery of social interactions in class X generated already meet the category is valid, practical, and effective.Penelitian pengembangan ini bertujuan untuk mengembangkan LKS materi perkalian matriks bercirikan penemuan terbimbing di kelas X SMK yang valid, praktis, dan efektif. Pengembangan LKS ini menggunakan model pengembangan 4-D yang terdiri atas empat tahap, tetapi dalam pengembangan LKS ini hanya akan dilakukan sampai tahap ketiga saja. Subjek uji coba pada penelitian pengembangan LKS ini adalah siswa kelas X SMK Putra Indonesia Malang. Berdasarkan hasil validasi LKS yang divalidasi oleh dua orang validator ahli dan satu orang praktisi, LKS yang dikembangkan memenuhi kategori valid. Berdasarkan hasil observasi terlaksananya LKS menunjukkan bahwa tingkat keterlaksanaan LKS mencapai kategori tinggi, sehingga LKS yang dikembangkan memenuhi kategori praktis. Berdasarkan nilai rata-rata penguasaan bahan ajar seluruh kelas yaitu 76, aktivitas penemuan terbimbing yang termasuk kategori baik, dan respon siswa terhadap LKS termasuk kategori positif, sehingga LKS yang dikembangkan memenuhi kategori efektif. Dengan demikian, LKS materi perkalian matriks bercirikan penemuan terbimbing di kelas X yang dihasilkan sudah memenuhi kategori valid, praktis, dan efektif.